Characterisation and saccharide mapping of polysaccharides from four common Polygonatum spp - Zhao, Ping; Li, Xia; Wang, Ying; Yan, Lanyi; Guo, Lanping; Huang, Luqi; Gao, Wenyuan (Carbohydrate polymers, 2020)
•Polysaccharides from PS, PC and PK were composed of pectins and fructans.•Polysaccharides from PO mainly consisted of fructans.•Polysaccharides from cultivated-type of Polygonatum spp. had less pectins.•Esterification were found in pectins from Polygonatum spp. Polysaccharides from 14 batches of Polygonatum sibiricum (PS), P. cyrtonema (PC), P. kingianum (PK) and P. odoratum (PO) were compared based on high-performance gel permeation chromatography (HPGPC) saccharide mapping, monosaccharide composition, molecular weight distribution and Fourier transform infrared (FTIR) spectra. Results showed that polysaccharides from PS, PC and PK exhibited two different molecular weight fractions and that one was more than 4.1 × 105 Da (P1) and the other was 2.8–5.4 × 103 Da (P2); while the polysaccharides from PO displayed only one main peak (P2). The analysis of monosaccharide composition and HPGPC saccharide mapping proved that P1 and P2 were composed of pectins and fructans, respectively. The FTIR spectra indicated that these polysaccharides had different degrees of esterification. This study provided a systematic profiling of polysaccharides of Polygonatum spp. and was helpful in understanding the varied functions of different Polygonatum spp., based on chemical composition.